Crude Glycerol for Monoolein Production using Nanotubes Supported Lipase - Artikah Muhammad Shahrin, Nur; Aziah Serri, Noor; Hana Hanif Abu Bakar, Noor; ., . (International Journal of Engineering and Technology, 2019)
A growing demand for biofuels as the alternative for fossil fuelsâ€™ extinction has produced abundance amount of crude glycerol as by-product in biofuel industries. Utilization of crude glycerol into a value-added product such as monoolein has been the focus for this present work. Instead of using free catalyst, the enzyme (lipase) used for this study was immobilized onto the halloysite nanotubes. The immobilized enzyme was characterized using TEM, BET and FTIR analysis. Further, the effect of time, temperature, agitation rate, and substrate molar ratio on monoolein production and fatty acid conversion were studied between free lipase and immobilized lipase using GC analysis. The best working conditions for immobilized lipase to produce monoolein was at 50oC, with 8 to 1 ratio of glycerol to oleic acid, agitated at 250 rpm for 18h. The amount of monoolein produced using immobilized lipase was highly comparable with free lipase, with ability to be reused and thermally stable at higher temperature.Â